Tests in special training of tennis-players: foreign experience - Сергієнко [Leonid Serhiyenko], Леонід Прокопович (Slobozhanskyi Herald of Science and Sport, 2013)
The article deals with the foreign experience of pedagogical control in special training of qualified tennis-players of different age. The model morphologic characteristics of high quality tennis-players both men and women are given. The technology of estimation of coordinative, strength, speed, aerobic abilities and flexibility in joints. Is described. This technology helps to define the special training of tennis-players